1)sin^2a+cos^2a+ctg^2a=1+cos^2a/sin^2a=1/sin^2a
2)cos^2a (1+tg^2a)=cos^2a+sin^2a=1
3)1-1/sin^2a=sin^2a-1/sin^2a=-cos^2a/sin^2a=-ctg^2a
4) cos^2B-cos^2Bsin^2B=cos^2B (1-sin^2B)=cos^2B
5) 1-cos^2B/sin^2B-1=-sin^2B/cos^2B=-tg^2B
6)(1-cos^2a)*(1+tg^2a)=1+tg^2a-cos^2a-sin^2a=-1-tg^2+1=-tg^2a
7)cosa/1+sina-cosa/1-sina=cosa-cosasina-cosa-sinacosa/1-sina^2=-2cosasina/cos^2a=-2sina/cosa=-2tga
8)(cosa+sina)^2-2sinacosa=cos^2a+2cosasina+sin^2a-2sinacosa=1
9)(1-sina)(1+sina)/cosa=1-sina^2/cosa=cosa
3
a)sin360=0
b)cos330=- √3/2
B) sin(-405)=- √2/2